Evaluation of the signal frequency with adaptive noise suppression in systems of acoustic sounding of the atmosphere - Карташов, В.М.; Тихонов, В.А.; Воронин, В.В.; Супрун, А.А. (Radiotekhnika, 2019)
The paper deals with the mathematical modeling of acoustic noise using models of autoregression and synthesis of autoregressive prediction filters for whitening and adaptive noise suppression. It is shown that the use of adaptive notch filters significantly reduces the effect of acoustic interference on the estimated peak frequency of the useful signal in acoustic sounding systems and significantly reduces its standard deviation.